The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2174/1567205012666150921100311
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Choline Supplementation: A Potential Prenatal Treatment for Down Syndrome and Alzheimer's Disease

Abstract: Although Down syndrome (DS) can be diagnosed prenatally, currently there are no effective treatments to lessen the intellectual disability (ID) which is a hallmark of this disorder. Furthermore, starting as early as the third decade of life, DS individuals exhibit the neuropathological hallmarks of Alzheimer’s disease (AD) with subsequent dementia, adding substantial emotional and financial burden to their families and society at large. A potential therapeutic strategy emerging from the study of trisomic mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 128 publications
3
87
0
Order By: Relevance
“…Since functional deficits associated with DS correspond with endpoints affected by MCS, we previously conducted a study to test the hypothesis that MCS would improve learning and attention in Ts65Dn offspring. This study yielded evidence for substantial cognitive benefits, as well as an improved regulation of negative affect in Ts65Dn mice (Moon et al, 2010; Strupp et al, 2016). …”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Since functional deficits associated with DS correspond with endpoints affected by MCS, we previously conducted a study to test the hypothesis that MCS would improve learning and attention in Ts65Dn offspring. This study yielded evidence for substantial cognitive benefits, as well as an improved regulation of negative affect in Ts65Dn mice (Moon et al, 2010; Strupp et al, 2016). …”
mentioning
confidence: 68%
“…Our group has demonstrated that supplementing the maternal diet with additional choline has numerous beneficial effects for Ts65Dn and 2N offspring, including improvements in attention, emotion regulation, spatial memory, hippocampal neurogenesis, and protection of cholinergic neurons in the MSN (Ash et al, 2014; Moon et al, 2010; Strupp et al, 2016; Velazquez et al, 2013). Choline supply is critical for the developing brain because it is a precursor of acetylcholine, a key neurotransmitter for regulating neuronal proliferation, differentiation, migration, maturation, plasticity, and survival, as well as synapse formation (Abreu-Villaca et al, 2011; Albright et al, 1999; Blusztajn, 1998; Cermak et al, 1999; Zeisel, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational brain changes may result from choline’s role as the precursor to phosphatidylcholine, a major constituent of neuronal cellular membranes, and, to a lesser extent, as a precursor of ACh, which is a key ontogenetic signal during development [34,51,57,102]. Additionally, long-term effects of early choline supplementation may be related to epigenetic factors with lasting effects on gene expression, secondary to choline’s role as a methyl donor [39,103105].…”
Section: Discussionmentioning
confidence: 99%
“…A potential treatment approach involves maternal dietary supplementation with choline, an essential nutrient involved in neural tube closure, organogenesis, central nervous system cell membrane synthesis, and methylation-dependent gene expression [36,3844]. MCS has both immediate and long-term beneficial effects in healthy disomic rats and mice [4457], and in rodent models of prenatal ethanol exposure, Rett syndrome, and status epilepticus [5863]. To explore the effects of early choline supplementation on cholinergic innervation and activity in the hippocampus of the adult brain, we used a MCS paradigm and studied adult male Ts65Dn and 2N offspring.…”
Section: Introductionmentioning
confidence: 99%